A rolling-sliding bench test for investigating rear axle lubrication. (May 2018) - Stump, Benjamin C.; Zhou, Yan; Viola, Michael B.; Xu, Hai; Parten, Randy J.; Qu, Jun
Abstract: An automotive rear axle is composed of a set of hypoid gears, whose contact surfaces experience a complex combination of rolling contact fatigue damage and sliding wear. Full-scale rear axle dynamometer tests are used in the industry for efficiency and durability assessment. This study developed a bench-scale rolling-sliding test protocol by simulating the contact pressure, oil temperature, and lubrication regime experienced in a dynamometer duty cycle test. Initial bench results have demonstrated the ability of generating both rolling contact-induced micropitting and sliding wear and the feasibility of investigating the impact of slide-to-roll ratio, surface roughness, test duration, and oil temperature on the friction behavior, vibration noise, and surface damage. This bench test will allow studying candidate rear axle lubricants and materials under relevant conditions. Highlights: A new rolling-sliding bench test with simulated contact pressure and lubrication regime in a dynamometer duty cycle test. Demonstrated ability of generating both rolling contact-induced micropitting and sliding wear. Correlated SRR, roughness, test duration, and oil temperature to friction behavior, vibration noise, and surface damage.